PENGARUH RASUL PAULUS DALAM SEJARAH KEKRISTENAN Sebelum â€“ Sesudah Pertobatan â€“ Tradisi - Tantiono, Paulus Toni (LOGOS, 2009)
The apostle Paul has been justifiably described as the first and greatest Christian theologian. His letters were among the earliest documents to be included in the New Testament and, as such, they shaped Christian thinking from the beginning. As a missionary, theologian, and pastor Paul wrestles with theological and ethical questions of his day in a way paradigmatic for Christian theology. After his â€œcallingâ€ as a missionary of the Gospel and Jesusâ€™ apostle, Paul builds all of his theologies based upon Christ. He â€œchristologizesâ€ his theologies. Since the beginning Paul has always been an uncomfortable and controversial figure in the history of Christianity. The accusation against the prophet Elijah by Israelâ€™s King Ahab, â€˜you troubler of Israelâ€™ (1 Ks. 18:17), could be levelled against Paul more fittingly than any other of the first Christians. Marcion, Irenaeus, Tertullian and Valentinus in the second century are only few examples of how his theologies can become controversial subjects. In fact until now Paulâ€™s theologies have remained one of the most disputable subjects in Christian theology either for Christians themselves or non-Christian believers.